Civil War in Yaman: Do Women and Children Have Human Rights Protection? - Gunawan, Yordan; Rahmanita, Fadhilah; Ode, Mahazanni Najwa Al-Asyifa (Faculty of Law, Universitas Pattimura, 2024)
Introduction: This article delves into the intricacies of the Yemen civil war, focusing on the human rights situation affecting women and children. The analysis underscores the severe challenges in safeguarding their rights due to limited access to essential services caused by the conflict. The article examines ongoing programs and policies to strengthen protection measures and reinforce global awareness of vulnerable populations in Yemen. Purposes of the Research: The research is dedicated to analyzing the gravity of the human rights crisis in civil war, especially for women and children. Highlighting the hardships they experience, proposing pragmatic solutions, and increasing international recognition of their plight. Identifying gaps in existing protection mechanisms, this research advocates for cooperative strategies that can ease the burden faced by the Yemeni and nurture a more promising future.Methods of the Research: Utilizes normative and legal methodologies to comprehensively explore the protection of human rights. A complete understanding of the challenges faced through a descriptive methodology, incorporating a literature review and case studies. Research information was drawn from relevant legal documents, media reports, and policy analysis.Results of the Research: The findings of this research unequivocally reveal that Yemeni women and children face enormous obstacles in securing their human rights in armed conflict. Acts such as murder, rape, and recruitment of child soldiers exacerbate this already dire situation. Engaging government and civil society efforts are urgently needed to advocate for and ensure the well-being of Yemeni women and children during this protracted conflict.